Chromatin-Independent Interplay of NFATc1 and EZH2 in Pancreatic Cancer - Shilpa Patil; Teresa Forster; Kristina Reutlinger; Waltraut Kopp; Lennart Versemann; Jessica Spitalieri; Jochen Gaedcke; Philipp Ströbel; Shiv K. Singh; Volker Ellenrieder; Albrecht Neesse; Elisabeth Hessmann (Cells, 2021)
Background: The Nuclear Factor of Activated T-cells 1 (NFATc1) transcription factor and the methyltransferase Enhancer of Zeste Homolog 2 (EZH2) significantly contribute to the aggressive phenotype of pancreatic ductal adenocarcinoma (PDAC). Herein, we aimed at dissecting the mechanistic background of their interplay in PDAC progression. Methods: NFATc1 and EZH2 mRNA and protein expression and complex formation were determined in transgenic PDAC models and human PDAC specimens. NFATc1 binding on the Ezh2 gene and the consequences of perturbed NFATc1 expression on Ezh2 transcription were explored by Chromatin Immunoprecipitation (ChIP) and upon transgenic or siRNA-mediated interference with NFATc1 expression, respectively. Integrative analyses of RNA- and ChIP-seq data was performed to explore NFATc1-/EZH2-dependent gene signatures. Results: NFATc1 targets the Ezh2 gene for transcriptional activation and biochemically interacts with the methyltransferase in murine and human PDAC. Surprisingly, our genome-wide binding and expression analyses do not link the protein complex to joint gene regulation. In contrast, our findings provide evidence for chromatin-independent functions of the NFATc1:EZH2 complex and reveal posttranslational EZH2 phosphorylation at serine 21 as a prerequisite for robust complex formation. Conclusion: Our findings disclose a previously unknown NFATc1-EZH2 axis operational in the pancreas and provide mechanistic insights into the conditions fostering NFATc1:EZH2 complex formation in PDAC.